A failed attempt to radically reduce inter-court sentencing disparities by legislation: Empirical evidence from Poland - Mamak, Kamil (European journal of criminology, 2022)
Sentencing disparities are widely covered in the literature on common law countries. In comparison, the literature on sentencing disparities in civil law countries is less extensive, and the literature is even more scarce in post-communist countries. Nevertheless, sentencing disparities exist in all of these countries. One of the goals of the 2015 criminal law reform in Poland was to limit sentencing disparities. This study compares trial outcomes from before and after the reform. We examine files from district courts in 13 cities in Poland for two offences: drug possession and drunk driving. Our findings demonstrate that there are significant differences in sentencing across courts, even in courts that are situated in the same city. The reform has changed the structure of the punishments but has not radically reduced sentencing disparities.